Bridging The Digital Divide: Internet Access And Farmer Poverty In East Java - Dias Satria; Christiayu Natalia (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
Poverty among farmers remains a structural challenge in agricultural development in Indonesia; low productivity and limited access to information technology are the main problems.  Addressing this issue is crucial for national food security and sustainable rural livelihoods. This study aims to examine the profile of poor farmers and analyze the effect of internet use on the risk of poverty among farmers in East Java Province. The data comes from the March 2023 National Socio-Economic Survey (Susenas) microdata, comprising 21.368 individual observations. The analysis method used is binary logistic regression due to the binary classification of the dependent variable, with model segregation based on urban and rural areas, implemented using Stata software. The results show that poor farmers generally come from the food crop subsector and are concentrated in certain areas such as Madura Island.  Digital literacy and internet utilization are still very low, while access to formal financing is also limited.  Internet access significantly reduces the poverty risk, with users being 2.72 times more likely to be non-poor, especially in urban areas. This study recommends different policy approaches between urban and rural areas to realize inclusive and adaptive agriculture in the digital era.